Qauranparqui of Susapaya: Tacna preceramic rock art - Umire Alvarez, Adán (2023)
The town of Susapaya presents excellent geographical environments, with plant and animal resources, which seven thousand years ago served as a habitable setting in the development of hunter-gatherers. The natural resources that support these scenarios were apparently also predictable as potential hunting areas, at the moment the area is a nature reserve dedicated to the protection of the guanaco (Lama guanicoe), considered one of the possible eligible resources in pre-ceramic hunting activities, perhaps preferred as higher visibility prey. The scene painted in Qauranparqui, with the figures of camelids, indicates the importance of the area. In addition, in a simple relationship in this area between the extensive presence of camelids (guanaco) and the figures represented on the rocky walls of Qauranparqui, it is proposed that they correspond precisely to the guanaco variety.